Pelatihan Literasi Digital Marketing melalui Media Facebook dan WhatsApp untuk Penggiat Pariwisata Desa Ranuyoso - Fredy Nugroho Setiawan; Mochamad Andhy Nurmansyah; Scarletina Vidyayani Eka (Jurnal Surya Masyarakat, 2024)
Merdeka Various types of processed products from fruit and plants in Ranuyoso Village, Lumajang Regency can be developed into one of the aspects that can support efforts to promote the village as a tourism village. Therefore, this community service was carried out to help realize the development of the tourism sector in the field of marketing processed fruit products from Ranuyoso. The activities were interviews on digital literacy with 3 members of the UPK (Activity Implementation Unit) which was formerly under the PNPM program (National Program for Community Empowerment), who are currently tasked with initiating the manufacture and marketing of processed agricultural products in Ranuyoso village, and continued with digital literacy training related to marketing the products they want to sell via social media. This training was also attended by several villagers who were interested in online marketing. The results of the interviews are used as a basis for formulating training materials. The training activities focus on strengthening and empowering human resources by providing understanding and training on the use of social media, including: a) knowledge about the current role of social media in tourism and economic activities, b) understanding the content of products marketed via social media; c) marketing the products via social media more effectively and efficiently. The training successfully draws enthusiasm from UPK members and community representatives, which is proven by the direct practice done by the participants in marketing processed food and beverage products via Facebook and WhatsApp.